Developmental Heterogeneity in Social Support Among Juvenile Offenders: relevance of Social Support Withdrawal for the Dulling of Maturational Decline in Offending - Wojciechowski, Thomas W. (Crime & delinquency, 2020)
Social support is a highly relevant predictor of offending. Despite this, little research has examined how this construct develops over time and how withdrawal of social support may result in "late bloomer" offending. This study used the Pathways to Desistance to data to test hypotheses related to these research questions. Group-based trajectory modeling was used to identify trajectories of social support, and ordinary least squares regression was used to determine the relevance of trajectory group assignment for predicting differences in offending between adolescence and adulthood. Results indicated that withdrawal of social support resulted in a dulling of the maturational decline in offending frequency typically observed following adolescence. Implications are discussed.